Upper Holocene Paleoceanography of Inner Miramichi Bay - Wagner, F.; Schafer, C. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1979)
Changes in sediment texture and in foraminiferal and molluscan assemblages observed in three vibraaores collected in Miromichi Tnner Boy reflect the development of a barrier island system across the mouth of the Bayt and the opening and closing of channels between the islands. The barrier island system apparently developed initially between 4400 and 3600 C14 years B.P. Opening and infilling of Buckleberry Gulley during the past 1300 years is indicated by changes in the proportions of estuarine and open bay assemblages of henthanic foraminifera. Mollusc and fora-minifera data do not always suggest the same paleoenvironmental conditions at any given place and time, but they are in good agreement with respect to the direction of paleoenvironmental trends.